PERAN SERTA MASYARAKAT TERHADAP KONSERVASI SUMBER DAYA ALAM HUTAN ADAT WONOSADI DI DUSUN DUREN KEC. NGAWEN KAB. GUNUNG KIDUL - , AL AJIIZ HASBUR ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Local wisdom to conserve the forest was the positive value that always must be conserved, nevertheless still was needed by the existence of the increase in the community's participation in the conservation program of nature resources that were held of the Adat Wonosadi Forest still really was needed to achieve the aim of the Adat Wonosadi Forest management, so as eventually the community will obtain the profit, as well as will guarantee conservation and the security of this wildlife reserve. Because of that this research had a purpose to: 1) Identify the level of the community's participation in conservation of nature resources in the Adat Wonosadi Forest